2020
DOI: 10.1186/s12887-020-02024-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of neonatal hypothermia and its associated factors in East Africa: a systematic review and meta-analysis

Abstract: Background: Neonatal hypothermia is a global health problem and a major factor for neonatal morbidity and mortality, especially in low and middle-income countries. Therefore, this systematic review and meta-analysis aimed to assess the prevalence of neonatal hypothermia and its associated factors in Eastern Africa. Methods: We used the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to search electronic databases (PubMed, Cochrane Library and Google Scholar; date of last s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…We used pre-specified inclusion criteria to further screen the full-text articles. Disagreements were resolved with third reviewer (GT) for the final decision on the selection of studies to be included in the analysis [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used pre-specified inclusion criteria to further screen the full-text articles. Disagreements were resolved with third reviewer (GT) for the final decision on the selection of studies to be included in the analysis [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The disagreement was resolved by the interference of a third reviewer. Studies were considered as high risk or poor quality, when it scored 3 and below [ 20 22 ] ( S2 Table ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review including 20,911 participants from 12 studies indicated a 57.2% prevalence of neonatal hypothermia in Eastern Africa 5 . Of note, hypothermia in low-resource settings involves both term and preterm infants 5,6 . In low-middle resource settings, neonatal hypothermia was associated with elevated mortality risk in both hospital and community studies [7][8][9][10][11][12] .…”
mentioning
confidence: 99%